A new Ag/Bi7Ta3O18 plasmonic photocatalyst with a visible-light-driven photocatalytic activity. Issue 19 (14th August 2017) - Li, HongWei; Zhu, Hekai; Wang, Meng; Min, Xin; Fang, Minghao; Huang, Zhaohui; Liu, Yan'gai; Wu, Xiaowen
Abstract: Abstract : A new plasmonic photocatalyst Ag/Bi7 Ta3 O18 was fabricated by photodeposition-hydrothermal method. The phase composition, microstructure, surface areas, average pore size, UV-vis diffuse reflection spectra, and photocatalytic activities of composite photocatalysts were investigated in detail. The results of the measurements indicated that the Ag 0 nanoparticle successfully loads on the surface of Bi7 Ta3 O18, and the 0.06 Ag/Bi7 Ta3 O18 photocatalysts exhibited the best photocatalytic activity for the degradation of Rhodamine B (RhB). The improved photocatalytic activity could be contributed to the localized surface plasmon resonance caused by the collective oscillation of the surface electrons of Ag nanoparticles. Additionally, the photocatalytic reaction mechanism was studied by photoluminescence photocurrent, and electron spin resonance analysis. As a result, the Ag nanoparticles onto the Bi7 Ta3 O18 surface enlarged the electron–hole separation, and the (˙OH) was the dominated active species of degradation RhB in the photocatalytic process.